HUBUNGAN REGULASI EMOSI TERHADAP PENERIMAAN DIRI SISWA KELAS XII DI PONDOK PESANTREN MIFTAHUL HUDA BOGOR - Maghfirah Qonitatunnisa; Putri Ria Angelina; M. Kholil Nawawi (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
both socially and emotionally. However, it was found that some students still experience difficulties in managing their emotions and show low levels of self-acceptance. This study aims to determine the relationship between emotion regulation and self-acceptance among students in this environment. The research uses a quantitative approach with a correlational method. The sample consisted of 65 students selected using a saturated sampling technique. The instruments used were an emotion regulation scale based on Gross's theory and a self-acceptance scale based on Jersild's theory. Based on the data analysis and discussion, it was found that the majority of 12th-grade students at Pondok Pesantren Miftahul Huda Bogor have a moderate level of emotion regulation, as evidenced by 42 respondents (64.6) being in the moderate category. Similarly, the level of self-acceptance among these students was also in the moderate category, with 33 respondents (50.8) falling into that group. Pearson correlation test results showed a positive and significant relationship between emotion regulation and self-acceptance, with a correlation coefficient of r 0.583 and a significance value of 0.001. This means that the higher the students’ ability to regulate their emotions, the higher their level of self-acceptance. Thus, the hypothesis in this study is accepted. This research suggests the need for the development of emotional regulation training programs to support the optimal development of students self-acceptance.